Factors influencing consumers’ intention to purchase products advertised on Facebook - Mert, Hasinat; Wan Jusoh, Wan Jamaliah (2018)
The aim of this study is to investigate the factors that influence consumers’ intention to purchase products advertised on Facebook. Facebook is a popular social media platform that is used by many including Malaysian. Users are also exposed to the numerous number of advertisements on Facebook. But what are the impact of Facebook advertising on users’ purchase intention? Therefore, based on the Theory of Reasoned Action, the relationship between attitude towards products advertised on Facebook, subjective norm and intention to purchase were examined. The study also investigated word of mouth and display advertising as antecedents to attitude. A total of 405 respondents participated in this study. SPSS and Smart-PLS were used to analyzed the data collected. Attitude and subjective norm, were found to be positive and significantly related to intention to purchase. For the antecedent of attitude, display advertising was positive and significant while word of mouth was found to be not significant. These findings should assist marketers selling and advertising on Facebook in developing better strategies and programs. They should understand that attitude is the most significant predictor of intention to purchase while display advertising greatly influence attitude towards products advertised on Facebook. The effect of family members and friends have a positive influence on individuals, especially in a collectivist society like Malaysia.